PENGARUH CELEBRITY ENDORSE, BRAND IMAGE DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Putra, Dafriyal Tri; Bahrun, Khairul (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The purpose of this study was to determine the effect of celebrity endorsement, brand image and consumer trust on purchasing decisions (a case study on consumers of Erigo clothes in Kepahiang District. This research uses descriptive research methods with quantitative data analysis. The population in this study was all Erigo clothing consumers in Kepahiang District, totaling 80 respondents. Based on the results of multiple linear regression, the regression equation Y = 6.733 + 0.195 (X1 ) + 0.408 ( X2) + 0.194 (X3) is obtained. The results and hypotheses show that celebrity endorsement shows a value of > (2,114 > 1,991) and (sig = 0.038 <0.050), brand image shows a value of > (6,300 > 1,991) and (sig = 0.000 <0.050), and consumer trust shows a value of > (2.218 > 1.991) and (sig = 0.030 <0.050). The results of the f test show that Fcount > Ftable, namely (55.674 > 3.9603) and (sig α = 0.000 <0.050), Simultaneously Celebrity Endorse, Brand Image and Consumer Trust Have a Significant Influence on Purchasing Decisions. Keywords: Celebrity Endorsement, Brand Image, Consumer Trust and Purchasing Decisions